O público e o privado no Ensino Médio em Santarém-Pará: qual o diferencial do desempenho cognitivo - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The need to increase the supply of Brazilian schooling was not accompanied by a concern with the quality of education offered. The first actions aimed at the implementation of a national basic education evaluation system in Brazil began in the 1980s, with the implementation of several educational reforms. During this period, Brazilian educational research was strongly influenced by the Coleman Report published in 1966 in the United States. This research has given new directions to both educational assessments and the allocation of social capital, revealing that education is part of a set of factors, and that research in the area needs to address social and school factors in educational inequalities. Against with a growing demand for measures that reverse the insufficient levels of learning revealed by the current evaluations of Brazilian basic education, we evoke here a discussion about the idea of education as a foundation for better individual formation and, thus, for the construction of a society fairer. The objective of this study was to compare the profile of cognitive performance in public and private high school students from two schools in the municipality of Santarém-Pará, from 2011 to 2017. This is a quantitative and qualitative research, with secondary data collection conducted from October 2018 to September 2019, with permission to consult the annual final results maps by the directors of the participating educational institutions, as well as from available data by the official national websites. The study showed significant differences in cognitive performance between the two schools. The analysis of variance (ANOVA) of the intra-school comparative of cognitive performance between shifts showed the t test with p<0.0001 for EPU and p<0.0054 for EPR. In the intra-school comparison of cognitive performance by series, the EPU showed a t test of p<0.0001 and p<0.0065 for EPR. The EPU proved to be the institution with the highest rates of red notes, reproctions, cancellations, retentions and withdrawals in the evaluated period. EPU students had greater difficulty in adapting to high school than EPR students, suggesting that they progress to high school with a deficient elementary school base, a fact reproduced over the years without any reversal measure, reflecting in the inequalities between the diagnosed performances in the two schools. The number of enrollments, as well as the number of students per class is much higher in the EPU, this is reflected in the higher Indicator of Teaching Effort in High School, suggesting that the quality of teaching may also be correlated to these variables. The research also suggests that the most important factor in determining the efficiency of teaching in the two institutions evaluated is more correlated to didactic-pedagogical, administrative, and extra-school factors, such as family aspects, for example, than to inputs themselves, being necessary more studies directed that to better characterize these results. Thus, the collective construction of a path of participation and co-responsibility for improving the quality of public education can be: a greater emphasis on the base of teacher education; and greater attention to deficiencies in primary education.
Keywords: Educação Básica; Aprendizagem Escolar; Avalição Educacional; Ensino Público; Ensino Privado; CNPQ::CIÊNCIAS DA SAÚDE::FARMÁCIA::TECNOLOGIA FARMACÊUTICA